OPTIMALISASI ANGGARAN PENDAPATAN DAN BIAYA SEKOLAH: KAJIAN DI SEKOLAH KOTA BANDA ACEH - Hirwan Jack (Jurnal Pencerahan, 2015)
In highly competitive era in the educational sector, the performance of private education unit manager, especially in terms of the quality of revenue and financing management process should be realized according to the plan to support the achievement of the expected goals. Therefore, all schools in Banda Aceh, as the manager it is necessary to measure the optimal level of school budget and revenues that have a functional planning, execution, control and supervision. Budget surplus was a dominant issue. This study focusses its analysis on the issues of schools’ budget in Banda Aceh, Indonesia. The study found that the performance of schools’ budget and revenues was not functioning optimally. Using the diagram method, this study then identified the causes of suboptimal performance, also undertake a review of policies of financing managemnet that already exist to seek improvements to optimize performance. By minimizing the causes that exist and by using the principles of Kaizen, which repairs, are carried out continuously and showed an increase in the performance of budget and revenues who proved the use costs of less than the plan during the empirical test period. By optimizing the performance of budget and revenues is very supportive for the school manager in Banda Aceh in formulating policies to achieve the desired goals.